Pemanfaatan Kacang Hijau Sebagai Sumber Zat Besi Dalam Upaya Pencegahan Anemia Prakonsepsi - Juhrotun Nisa; Adevia Maulidya Chikmah; Kharisma Anggra Lorenza; Kiki Rizki Amalia; Tri Agustin (Universitas Muhammadiyah Semarang, 2020)
High risk groups experience anemia, namely adolescents, especially young women, this is due to the need for iron absorption peaking at the age of 14-15 years while young men, experiencing peak absorption of iron one or two years later. The main risk factors for iron deficiency anemia are low iron intake, poor absorption of iron, and periods of life when the need for iron is high. Food fortification is the most effective way to prevent iron deficiency. One of the foods that can prevent iron is green beans. Consuming 2 cups of green beans every day means consuming 50% of the daily requirement of iron, 18 mg and can increase hemoglobin levels for 2 weeks. The purpose of this PKM is to provide an alternative picture of food in increasing hemoglobin levels in adolescents. The method used in this PKM is screening anemia through examination of hemoglobin and health education in young women in SMK 1 Tegal City. PKM results show that there is an increase in adolescent knowledge about anemia, the number of adolescent girls experiencing anemia is 35% of the total respondents. Iron is the main nutrient that plays an important role in the synthesis of hemoglobin so that the lack of iron intake obtained from food causes hemoglobin levels to decrease.